Effects of a mucoadhesive formulation containing curcuma longa l. on oral wound healing - Danilevicz, Chris Krebs; Wagner, Vivian Petersen; Webber, Liana Preto; Schmidt, Tuany Rafaeli; Alonso, Ellen Cristine Pineze; de Mendonça, Elismauro Francisco; Valadares, Marize Campos; Marreto, Ricardo Neves; Martins, Manoela Domingues (Clinical and Biomedical Research, 2021)
Introduction: The aim of this study was to investigate the effects of a topical mucoadhesive formulation with Curcuma longa L. extract (MFC) on oral wound healing. Methods: Seventy-two Wistar rats were randomly assigned to 3 groups: Control, Vehicle, and MFC. Traumatic ulcers were made on the dorsum of the tongue with a 3-mm diameter punch. Vehicle and MFC groups received application of the products twice a day, while animals in the control group were cared for in identical conditions but received no product application. Six rats in each group were euthanized at days 3, 5, 10, and 14. Percentage of repair was calculated based on wound area. HE-stained histological sections were obtained for semi-quantitative analysis of re-epithelization and inflammation. Results: Clinical findings revealed that at days 3 and 5, animals from the MFC group exhibited a significantly higher percentage of wound repair. At day 5, animals from this group also demonstrated a significant increase in the degree of re-epithelization and inflammation. Conclusions: MFC is capable of accelerating oral wound repair in an in vivo model by modulating the inflammatory process and stimulating epithelial proliferation.